Smooth operating and other social acts - Williams, Roland Leander, 1953- (Albany, NY : State University of New York Press, 2022)
An engaging homage to African American resilience and resourcefulness in US literature and culture.
Prologue: On the Sly -- Birth of Cool -- Standards and Practices -- Two of Kind -- Game of Charades -- Old Black Magic -- Lost in Translation -- Learning the Ropes -- Blind Man's Bluff -- Dress for Success -- Postscript: On One's Game.
Description based upon print version of record.
JSTOR
Keywords: American fiction -- 19th century -- History and criticism; American fiction -- 20th century -- History and criticism; African Americans in literature; Stereotypes (Social psychology) in literature; Role playing in literature; Race relations in literature; Slavery in literature; Roman américain -- 19e siècle -- Histoire et critique; Roman américain -- 20e siècle -- Histoire et critique; Noirs américains dans la littérature.; Stéréotypes dans la littérature.; Jeu de rôle dans la littérature.; Relations raciales dans la littérature.; Esclavage dans la littérature.; African Americans in literature; American fiction; Race relations in literature; Role playing in literature; Slavery in literature; Stereotypes (Social psychology) in literature; 1800-1999; Criticism, interpretation, etc; Literary criticism; Critiques littéraires.